Identification of Hub Genes Associated With the Development of Stomach Adenocarcinoma by Integrated Bioinformatics Analysis - Zhang, Kehui; Wang, Jian; Zhu, YingYing; Liu, Xiaolin; Li, Jiacheng; Shi, Zhe; Cao, Mengxing; Li, Yong (Frontiers in Oncology, 2022)
Objective This study was conducted in order to gain a better understanding of the molecular mechanisms of stomach adenocarcinoma (STAD), which is necessary to predict the prognosis of STAD and develop novel gene therapy strategies. Methods In this study, the gene expression profile of GSE118916 in the Gene Expression Omnibus (GEO) and The Cancer Genome Atlas Program (TCGA) was used to explore the differential co-expression genes of STAD and normal tissues. Results A total of 407 STAD samples were collected, consisting of 375 from stomach adenocarcinoma tissues and 32 from normal tissues, as well as RNA-seq count data for 19,600 genes. Forty-two differentially expressed genes were screened by weighted gene co-expression network analysis (WGCNA) and differentially expressed gene analysis. According to the functional annotation analysis of the clusterProfiler R package, these genes were analyzed for GO function enrichment, digestion (biological process), tube bottom material membrane (cell component), and oxidoreductase activity (molecular function). The KEGG pathway was enriched in gastric acid secretion and chemical carcinogenesis. In addition, Cytoscape’s cytoHubba plug-in was used to identify seven hub genes (EWSR1, ESR1, CLTC, PCMT1, TP53, HUWE1, and HDAC1) in a protein–protein interaction (PPI) network consisting of 7 nodes and 11 edges. Compared with normal tissues, CLTC and TP53 genes were upregulated in stomach adenocarcinoma (P < 0.05). TP53 was expressed differently in stages II and IV, EWSR1 was expressed differently in stages II and III, and ESR1 was expressed differently in stages I–III. Among the seven hub genes, Kaplan–Meier analysis and TCGG showed that the expression levels of HDAC1 and CLTC were significantly correlated with OS in patients with stomach adenocarcinoma (P < 0.05). GEPIA2 analysis showed that ESR1 expression was closely correlated with OS and DFS in gastric adenocarcinoma (P < 0.05). Then, the expression of the genes and their correlations were revealed by the R2 Platform (http://r2.amc.nl). Finally, we collected 18 pairs of gastric mucosal tissues from normal people and cancer tissues from patients with stomach adenocarcinoma. The expression levels of the above seven hub genes and their relative protein expression were detected by RT-PCR and immunohistochemistry (IHC). The results showed that the gene and protein expression levels in stomach adenocarcinoma tissues were increased than those in the normal group. Conclusion In summary, we believe that the identified hub genes were related to the occurrence of stomach adenocarcinoma, especially the expression of ESR1, HDAC1, and CLTC genes, which are related to the prognosis and overall survival of patients and may become the potential for the future diagnosis and treatment of STAD.